Cost Estimations of Managing Adverse Drug Reactions in Hospitalized Patients: A Systematic Review of Study Methods and Their Influences - Siti Fauziah Abu; Asrul Akmal Shafie; Haarathi Chandriah (MDPI AG, 2023)
This study aimed to systematically review and explore the impact of study methods on the cost of managing adverse drug reactions (ADRs) among hospitalized patients to guide policymakers and researchers. A literature search was conducted in MEDLINE, EMBASE, CINAHL, Cochrane Library, and Google Scholar. The search was restricted to studies from 2000 to 2017. Two authors independently reviewed the studies, assessed their risk of bias, and extracted information for analysis. Data abstraction was based on the study design, ADR reporting, and costing approaches. Of 677 studies identified, 12 were included for analysis. All studies defined ADR according to WHO classifications. The percentage of admission due to ADR ranged from 0.03% to 17.11%. All studies adopted a healthcare provider perspective, using either a micro-costing (n = 7), case-mix group costing (n = 3), or average-per-diem costing (n = 2) approach. The cost per ADR widely fluctuated from USD 65.00 to USD 12,129.90 based on various factors. The micro-costing approach generally had a lower cost compared to other approaches. The cost per ADR in high-income countries was also 10 times higher than in lower- or middle-income countries. This study evidenced that the methodological heterogeneity across studies has resulted in a wide range of cost estimations for ADR management.